Comparison of the photoactivities of two commercial titanium dioxide powders in the degradation of 1,4-dioxane - M. Mehrvar; W. A. Anderson; M. Moo-Young (International Journal of Photoenergy)
Two different commercial photocatalysts, Degussa P25 and Hombikat UV 100, were used to degrade 1,4-dioxane photocatalytically in an annular slurry photoreactor. The optimum photocatalyst loading for Degussa P25 was found to be 1.5 g L-1 while for Hombikat UV 100 was between 3.0−4.0 g L-1. The photoactivity of Degussa P25 is higher than that of Hombikat at lower photocatalyst loadings whereas it is lower at higher photocatalyst loadings. This was found both experimentally and also by mathematical modeling of the radiation within the photoreactor zone. The photoactivity of UV 100 titanium dioxide was found to be twice that of Degussa P25 at optimum loadings.